Strengthening Mental Health Literacy Character Education at Smpit Permata Insani - Supini; Alia Nabilah; Dea Puspita Aurellia; Via Octaviani; Octaviana Sitorus; Arif Budi Sunjaya; Muhidin Muhamad Jaelani; Helen Rizki Amalia; Hijrat, Abdullah; Rumi Arny Ompusunggu; Maya Fharsita Putri; Galuh Kumara (PT FORMOSA CENDEKIA GLOBAL, 2024)
Literacy is a person's ability to read and write, which contributes to the formation of a student's character. Health is defined as a condition in which a person can overcome challenges to achieve happiness both in this world and in the afterlife, which can be influenced by each person's character. Character is something that comes naturally to everyone. Family, school and society are some of the factors that shape a person's character, not innate character. This article presents the results of Community Service activities with the theme